Development of Crowdlending for SME in Colombia under A2Censo Platform - Zamora - Morantes, Carlos Hildar; Oviedo, Elizabeth (Universidad Francisco de Paula Santander, 2023)
The 4.0 revolution, the constant crises that surround business development that impact the country, and the search for opportunities for small investors with low resources force not only to modernize but also to change the idea of credit as a mechanism that leverages opportunities, leaving aside the rules of a "sole" offeror or financial contributor, which can influence the exclusion or limitation of the amount requested by the borrower, so that it becomes a mechanism accessible to proposals, real over time, with the contributions of different investors and the active support of the intermediary for their achievements of SMEs. This descriptive work aims to present the characterization of Crowdlending in Colombia, contrasting it with other investment platforms based on the documentary review. Broadly, the presence of "collective loans" allows SMEs (more small companies, less than five years old and in the manufacturing sector) to have accessible credit, allowing them, through the support of the platform, to supply their working capital needs.